Current Challenges with their Evolving Solutions in Surgical Practice in West Africa : A Reader - Clegg-Lamptey, J. N.; Dakubo, J. C. B.; Essuman, V. A.; Archampong, E. Q. (Book collections on Project MUSE., 2013)
Worldwide, there is a plethora of study materials in the form of authoritative review articles on disease entities afflicting the Western world but relatively few publications exploring similar problems confronting the developing countries, where resource limitation adds an extra dimension to the challenges facing the clinician. The contributions in this Reader address common surgical challenges and what measures have evolved to countenance these problems. This therefore addresses "Current Surgical Practice", placing emphasis on the principles underlying the consensus opinions prevailing in surgical management. The approach is practical, avoiding the minutiae of procedures for which appropriate references detailing such information are provided. The contributions have come from a broad suave of critical management problems in the salient fields of surgery. Regrettably some urgent areas of public interest are not covered but it is clear that this volume represents the beginning of a process, yea, the initiation of an epoch of Recent Advances in Surgical Practice; we are confident that such yawning gaps in coverage would soon be made good by subsequent developments, stimulated by issuance of this publication.